Integrating Multiple Intelligences and deep learning for transformative Islamic Religious Education - Ahmad Asron Mundofi (Himpunan Pengembang Kurikulum Indonesia, 2026)
Islamic Religious Education (IRE) plays a crucial role in fostering moral and spiritual values among students. However, classroom practices often remain focused on the transmission of normative knowledge, limiting opportunities for meaningful understanding and internalization of values. While previous research has examined the application of Multiple Intelligences (MI) and deep learning in educational contexts, these approaches are rarely integrated into a coherent IRE curriculum framework. This gap highlights the need for a curriculum model that accommodates students' diverse potential while fostering deeper engagement with Islamic teachings. This study explores the transformation of the IRE curriculum through the integration of MI and deep learning pedagogy to foster meaningful learning. Using a qualitative Design-Based Research approach, data were collected from teachers, students, and the IRE curriculum coordinator through interviews, observations, student reflections, and document analysis. Findings indicate that integrating MI with deep learning shifts IRE instruction from a transmission model to a reflective, contextual learning model. This integration supports differentiated learning experiences, strengthens conceptual understanding, and facilitates the internalization of Islamic values. This study proposes a transformative Islamic Education curriculum model that contributes to curriculum innovation and value-based education in 21st-century Islamic education. Abstrak Pendidikan Agama Islam (PAI) memainkan peran penting dalam menumbuhkan nilai-nilai moral dan spiritual pada murid. Namun, praktik di kelas sering kali tetap berfokus pada penyampaian pengetahuan normatif, sehingga membatasi peluang untuk pemahaman yang bermakna dan internalisasi nilai. Meskipun penelitian sebelumnya telah meneliti penerapan Kecerdasan Majemuk dan pembelajaran mendalam dalam konteks pendidikan, pendekatan ini jarang diintegrasikan ke dalam kerangka kurikulum Pendidikan Agama Islam yang koheren. Kesenjangan ini menyoroti kebutuhan akan model kurikulum yang mengakomodasi potensi murid yang beragam sekaligus mendorong keterlibatan yang lebih mendalam dalam ajaran Islam. Penelitian ini mengeksplorasi transformasi kurikulum Pendidikan Agama Islam melalui integrasi Kecerdasan Majemuk dan pedagogi pembelajaran mendalam untuk mendorong pembelajaran yang bermakna. Dengan menggunakan pendekatan Penelitian Berbasis Desain (Design-Based Research) kualitatif, data dikumpulkan dari guru, murid, dan koordinator kurikulum Pendidikan Agama Islam melalui wawancara, observasi, refleksi murid, serta analisis dokumen. Temuan menunjukkan bahwa integrasi Kecerdasan Majemuk dengan pembelajaran mendalam menggeser pengajaran Pendidikan Agama Islam dari model transmisi menjadi pembelajaran yang reflektif dan kontekstual. Integrasi ini mendukung pengalaman belajar yang terdiferensiasi, memperkuat pemahaman konseptual, dan memfasilitasi internalisasi nilai-nilai Islam. Studi ini mengusulkan model kurikulum PAI transformatif yang berkontribusi pada inovasi kurikulum dan pendidikan berbasis nilai dalam pendidikan Islam abad ke-21. Kata Kunci: kecerdasan majemuk; pembelajaran mendalam; pendidikan Islam; transformasi kurikulum